EVALUASI EFEKTIVITAS PENGGUNAAN APLIKASI OPEN VIRTUAL PRIVATE NETWORK (OVPN) DI UNUSA DENGAN METODE DELONE DAN MCLEAN - Ahmad Mujaab Syafiq Amiruddin; Fajar Annas Susanto; Tri Deviasari Wulan; Ima Kurniastuti (Universitas Islam Lamongan, 2023)
NU University Surabaya utilizes a helping application, namely the implementation of OVPN in Unusa for access to learning. In this study, an evaluation of the system was carried out using the Delone and Mclean methods. The focus of the research is the use of an application according to the needs of the user. The Delone and Mclean method consists of 6 variables of system quality, information quality, service quality, usage, user satisfaction and net benefit. The stages of this study are problem identification, determination of research respondents, creation of questionnaires using Delone and Mclean, dissemination of questionnaires, data processing, preparation of results and analysis. The results of SEM measurements on smartPLS from 254 respondents showed that there were 6 hypotheses accepted and 3 hypotheses rejected with t-statistical details greater than 1.96, namely The Quality of Information and Use has a Path Coefficient value of 0.445 with a t-statistical value of 5,207, the Quality of Service and Use has a Path Coefficient value of 0.441 with a t-statistical value of 4,932, Information Quality with User Satisfaction has a Path Coefficient value of 0.232 with a t-statistical value of 2.257, User Use and Satisfaction has a Path Coefficient value of 0.572 with a t-statistical value of 5.994, User Satisfaction and Net Benefit has a Path Coefficient value of 0.338 with a t-statistical value of 3.432, Net Usage and Benefits have a Path Coefficient value of 0.539 with a t-statistical value of 5.596.